The wanderer - Carr, Robyn (Carr, Robyn. Thunder Point novel., 2013)
Nestled on the Oregon Coast is a small town of rocky beaches and rugged charm. Locals love the land's unspoiled beauty. Developers see it as a potential gold mine. When newcomer Hank Cooper learns he's been left an old friend's entire beachfront property, he finds himself with a community's destiny in his hands. Cooper has never been a man to settle in one place, and Thunder Point was supposed to be just another quick stop. But Cooper finds himself getting involved with the town. And with Sarah Dupre, a woman as complicated as she is beautiful. With the whole town watching for his next move, Cooper has to choose between his old life and a place full of new possibilities. A place that just might be home.